Carbon credits for solid biofuels in Latin America: a computational tool based on Circular Bioeconomy principles - Farrapo Junior, Antonio Carlos (Universidade Federal de São Carlos, 2025)
The accelerating global population growth and the burgeoning demand for products forecasted by 2030 necessitate a sustainable transformation in production and consumption patterns to avert ecological catastrophe. Recognizing this urgency, the United Nations (UN) Agenda 2030 emphasizes the need for a Bioeconomy paradigm shift, aiming to reconcile economic growth with environmental stewardship. Within this framework, Bioenergy emerges as a pivotal component, encompassing renewable energy derived from biological sources, notably solid biofuels like biomass pellets and briquettes. Latin America, endowed with abundant biomass resources, has experienced notable growth in solid biofuel production. However, the region continues to face a significant gap in methodological harmonization and policy recognition of these biofuels within carbon credit mechanisms. To address this gap, a life cycle-based methodological framework was developed to estimate the carbon intensity and decarbonization potential of solid biofuels. Inspired by Brazil’s RenovaBio program and its RenovaCalc calculator, a novel tool, namely BioCalc, was designed to quantify greenhouse gas emissions and simulate carbon credit generation for pellets and briquettes. This doctoral thesis is structured into six chapters, four of which are presented in the form of scientific articles. These chapters address global bioenergy policy analysis, comparative assessment of carbon allocation methodologies, evaluation of transportation-related emissions in export contexts, and the design and application of the BioCalc tool to estimate carbon intensity and decarbonization credit potential for solid biofuels. Modeling results demonstrate substantial variability in greenhouse gas emissions and credit generation depending on the methodological approach adopted. Estimated decarbonization potentials ranged from 3.1 to 6.2 million tCO₂e per year, with associated revenue potential between USD 35.8 million and USD 103.9 million annually, highlighting the financial significance of methodological transparency and harmonization. By combining policy analysis, life cycle modeling, and computational innovation, the work contributes a replicable and policy-relevant framework to support the quantification and market integration of solid biofuels. The outcomes provide strategic insights for incorporating pellets and briquettes into national decarbonization programs, such as RenovaBio and the Brazilian Emissions Trading System (SBCE), as well as into emerging mechanisms established under Article 6 of the Paris Agreement. More broadly, the findings underscore the crucial role of circular economy principles and methodological clarity in promoting sustainable energy transitions in Latin America and globally.
Créditos de carbono para biocombustíveis sólidos na América Latina: uma ferramenta computacional baseada em princípios da Bioeconomia Circular
Créditos de carbono para biocombustibles sólidos en América Latina: una herramienta computacional basada en principios de la Bioeconomía Circular
Keywords: Avaliação do ciclo de vida; Gases de efeito estufa; Políticas de energia renovável; Mercado de carbono; Biomassa; Life cycle assessment; Greenhouse gas emissions; Renewable energy policy; Carbon market; Biomass; ENGENHARIAS::ENGENHARIA DE PRODUCAO; OUTROS